Synthesis and Non-linear Optical Properties of Two New Tridentate Mono Azo Schiff-Base Compounds - Sheikhshoaie, Iran; Hosein, Mohammad; Monadi, Niaz (Asian Journal of Chemistry, 2010)
In the present work, two dissymmetric tridentate mono azo Schiff base ligands 5-((4-methyl phenyl)azo)-N-(N,N-dimethyl ethylamine) salicylaldimine and 5-((4-nitro phenyl) azo)-N-(N,N-dimethyl ethylamine) salicyl- aldimine were prepared by the reaction of precursor ligands with appropriate N,N-dimethyl ethylamine and characterized by FTIR, 1H NMR, 13C NMR, C, H and N elemental analyses and UV-Vis spectroscopy methods. In the other part of this work, some theoretical calculations were done on the structures by semi-empirical and ab-initio methods using AM1, PM3 and MINDO/1 Hamiltonians and the geometries of two synthesized tridentate ligands were optimized and then the non-linear optical properties of these ligands were characterized by theoretical calculations.